FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT APARATUR SIPIL NEGARA (ASN) UNTUK MELAKUKAN TINDAKAN WHISTLE-BLOWING PADA PEMDA PROPINSI PAPUA - Wakerkwa, Rodika; Fallah, Syaikhul; Safkaur, Otniel (Fakultas Ekonomi, Universitas Cenderawasih, 2018)
This study examines factors affecting the interest of state civil servants to undertake whistle-blowing action on local governments of Papua Province. The population in this study is the State Civil Servants (ASN) on local governments of Papua Province, with 120 number of people as sample in this research. Multiple regression analysis techniques is used to analysis, discuss and testing the hypothesis from the data collection. This research find that variabel of organization commitment has a significant and negative effect on the interest of state civil servants to undertake Whistle Blowing action. Thus it can be explained that, in high and low commitment of organzation environment which dominated by employees at SKPDs in government of Jayapura city that have lowered interest to undertake Whistle Blowing action. Then, varibale of Attitude has a significant effect on the Interest of Whistle Blowing action, which the attitude of the existing employees will increase the interest to Blow the Whistle at the SKPDs’ employees in the government of Jayapura city. Similarly, Personal Cost variabel has a significant affect on the interest of state civil servants to attempt a Whistle Blowing action, it can be seen that when there is a sufficient personal cost in the employees of SKPD in the government of Jayapura city, it will increase the interest in Blowing the Whistle. While, the degree of seriousness also has a significant influence on the employees to attempt a Whistle Blowing interest. This means that the increasing interest in Blowing Whistle among employees are required to enhance the degree of seriousness in conducting Interest of Blowing a Whistle at SKPD in the government of Jayapura city.